2020
DOI: 10.21037/atm.2020.03.98
|View full text |Cite
|
Sign up to set email alerts
|

Identification of m6A-related genes and m6A RNA methylation regulators in pancreatic cancer and their association with survival

Abstract: Background: N6-methyladenosine (m6A) modification holds an important position in tumorigenesis and metastasis because it can change gene expression and even function in multiple levels including RNA splicing, stability, translocation and translation. In present study, we aim to conducted comprehensive investigation on m6A RNA methylation regulators and m6A-related genes in pancreatic cancer and their association with survival time.Methods: Based on Univariate Cox regression analysis, protein-protein interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 36 publications
0
59
0
Order By: Relevance
“…We found that the significantly enhanced transcript of WTAP (as components of the mammalian m6A methyltransferase complex) was associated with downregulation of ECM genes in GO specimens. Taken together, it seems plausible that the expression of ECM genes in GO specimens may be regulated by RNA methylation [36][37][38]. In fact, WTAP might especially contribute to the decreased expression of ECM genes [37,39].…”
Section: Discussionmentioning
confidence: 98%
“…We found that the significantly enhanced transcript of WTAP (as components of the mammalian m6A methyltransferase complex) was associated with downregulation of ECM genes in GO specimens. Taken together, it seems plausible that the expression of ECM genes in GO specimens may be regulated by RNA methylation [36][37][38]. In fact, WTAP might especially contribute to the decreased expression of ECM genes [37,39].…”
Section: Discussionmentioning
confidence: 98%
“…Among these, N6-methyladenosine (m6A) is the best understood and frequent mark of mRNA, and the functions of which ranges from pre-mRNA processing, translation, miRNA biogenesis to mRNA decay [30] . The importance of METTL3 and ALKBH5 in the development and progression of pancreatic cancer have pointed out [31 , 32] . By contrast, much less research has been conducted on m5C, which was detected in tRNAs and rRNAs and more recently in poly(A)RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that a number of m6A RNA methylation regulators were expressed at higher levels in the high-mRNAsi groups of both colon and rectal cancer patients. YTHDF1, a "reader" of m6A methylation, plays a signi cant role in regulating the colon cancer stem cell-like features via the Wnt/β-catenin pathway and regulating the translation of selectively recognized mRNAs [65]. Furthermore, ALKBH5 was found to promote tumor formation and increase cancer cell stemness by regulating mRNA stability of pluripotency factors via m6A demethylation in hypoxic environments [66].…”
Section: Discussionmentioning
confidence: 99%